Kebijakan Pengentasan Kemiskinan Melalui Dana Desa dan Penguat Otonomi Desa - Citra Etika (COSTING : Journal of Economic, Business and Accounting, 2018)
The Village Fund is one of the policies made by the government to alleviate poverty in the village and strengthen village autonomy. The use of Village Funds is used in the field of village development and the field of community empowerment, of the total Village Funds channeled to the Village 75 percent for the development sector while for the community empowerment sector only 25 percent so that the way to overcome poverty is still relatively small. The objectives to be achieved in this study are to find out about poverty reduction policies through the Village Fund and strengthening village autonomy in Prabumulih City. The research was conducted in the villages of Jungai, Sinar Rambang, Rambang Senuling, Karangan, Talang Batu, Kemang Tanduk. The method in this study is a qualitative method using Focus Group Disussion (FGD), interviews with parties related to poverty alleviation issues (officials of the Village Consultative Body, Village Chief, Village Treasurer, Village Secretary, Planning Head, Head of Public division, head of finance division, Head of Government, Head of People's Welfare, Head of construction division, community leaders). The results of this study are that the Prabumulih City Government has implemented policies by gradually channeling Village Funds based on village performance. However, villages in Prabumulih City have not fully focused on poverty alleviation efforts. This can be seen from the APB Village Responsibility Report at the expenditure point in the field of community empowerment which is used for “posyandu” empowerment activities, Up2K, SisKeuDes training activities. Furthermore, the number of poor people in Prabumulih City is still high, namely BPS data of 43,464 people. Keywords: Poverty Alleviation Policies, Village Funds, Village Autonomy